Scalable fabrication of polymeric dissolving microneedles for optimized ALA delivery in photodynamic therapy - Bejar, Dianeth Sara Lima; Requena, Michelle Barreto; Stringasci, Mirian Denise; Garcia, Marlon Rodrigues [UNESP]; Ayala, Erika Toneth Ponce; Barreiro, Juliana Cristina; Pratavieira, Sebastião; Bagnato, Vanderlei Salvador (Elsevier, 2025)
Topical photodynamic therapy (PDT) is a minimally invasive, clinically approved treatment for non-melanoma skin cancer that relies on the conversion of photosensitizer (PS) precursors such as 5-aminolevulinic acid (ALA) into protoporphyrin IX (PpIX), followed by light activation. However, the low skin penetration of topically applied ALA cream remains a major limitation, restricting effective PpIX accumulation in deeper tumor layers. To address this challenge, we produced dissolving microneedles (DMN) as an alternative intradermal delivery platform. Two mold types were evaluated for DMN fabrication, one with a slight edge (DMNe) and another without edges (DMNf), both maintaining a conical tip geometry. DMN were prepared with a formulation containing initially 10% ALA and 20% Gantrez® AN-139 polymer in water, produced in a few steps, and characterized. In vitro insertion studies demonstrated consistent penetration depths of approximately 250μm with minimal tip deformation. DMNf showed a better penetration efficiency than the DMNe and cream groups, and mass spectrometry confirmed uniform ALA distribution. In vitro assays in darkness confirmed the formulation's biocompatibility with tumor cells. In a murine xenograft model of nodular epidermoid carcinoma, DMN-mediated ALA delivery generated up to twice the amount of PpIX in deeper tumor regions and also caused greater PDT damage compared to cream application. These findings highlight DMN as a promising approach to enhance PDT efficacy, especially for thicker or nodular skin lesions, by enabling superior and uniform intradermal drug delivery.